Teacher readiness and institutional support in raudatul atfal: descriptive analysis of independent curriculum implementation - Huliyah, Muhiyatul; Muhtadi, Didi; Imroatun, Imroatun; Bastian, Abda Billah Faza Muhammadkan (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: The Independent Curriculum is a transformative initiative in the Indonesian education system, emphasizing flexibility, contextual teaching, and holistic child development. However, its implementation is a challenge for PAUD teachers, especially in Raudatul Lembaga Atfal (RA). To effectively address these challenges, a comprehensive understanding of teacher readiness and institutional support is needed.Objective: This study aims to analyze the readiness of RA teachers and institutional factors that support the implementation of the Independent Curriculum in Tangerang Regency, Indonesia. This study identifies key gaps in teacher competency and systemic drivers that are important for improving curriculum implementation.Methods: This study used a descriptive research design and involved 103 RA teachers from various locations. Data were collected through structured surveys and semi-structured interviews, focusing on various dimensions of teacher readiness, such as pedagogical competence, curriculum knowledge, technology proficiency, and adaptive capacity.Results: The findings highlight strong pedagogical skills but also reveal significant curriculum knowledge and technology gaps, especially in rural areas. The study's novelty lies in its integration of teacher readiness and institutional support, offering fresh insights into improving curriculum implementation.Conclusion: This study fills a research gap by examining individual and institutional factors influencing PAUD teacher readiness. Theoretically, it integrates readiness with institutional support, enhancing educational frameworks. Practically, it provides strategies for policymakers and leaders to improve PAUD through robust support systems